Evaluation of quality of life according to asthma control and asthma severity in children and adolescents - Natasha Yumi Matsunaga; Maria Angela Gonçalves de Oliveira Ribeiro; Ivete Alonso Bredda Saad; André Moreno Morcillo; José Dirceu Ribeiro; Adyléia Aparecida Dalbo Contrera Toro (Jornal Brasileiro de Pneumologia, 2015)
ABSTRACT OBJECTIVE: To evaluate quality of life according to the level of asthma control and degree of asthma severity in children and adolescents. METHODS: We selected children and adolescents with asthma (7-17 years of age) from the Pediatric Pulmonology Outpatient Clinic of the State University of Campinas Hospital de Clínicas, located in the city of Campinas, Brazil. Asthma control and asthma severity were assessed by the Asthma Control Test and by the questionnaire based on the Global Initiative for Asthma, respectively. The patients also completed the Paediatric Asthma Quality of Life Questionnaire (PAQLQ), validated for use in Brazil, in order to evaluate their quality of life. RESULTS: The mean age of the patients was 11.22 ± 2.91 years, with a median of 11.20 (7.00-17.60) years. We selected 100 patients, of whom 27, 33, and 40 were classified as having controlled asthma (CA), partially controlled asthma (PCA), and uncontrolled asthma (UA), respectively. As for asthma severity, 34, 19, and 47 were classified as having mild asthma (MiA), moderate asthma (MoA), and severe asthma (SA), respectively. The CA and the PCA groups, when compared with the NCA group, showed higher values for the overall PAQLQ score and all PAQLQ domains (activity limitation, symptoms, and emotional function; p < 0.001 for all). The MiA group showed higher scores for all of the PAQLQ components than did the MoA and SA groups. CONCLUSIONS: Quality of life appears to be directly related to asthma control and asthma severity in children and adolescents, being better when asthma is well controlled and asthma severity is lower.